Kinetic and equilibrium studies of urea adsorption onto activated carbon: Adsorption mechanism. Issue 7 (3rd July 2017) - Kameda, Tomohito; Ito, Saya; Yoshioka, Toshiaki
ABSTRACT: We found that activated carbon effectively removed urea from solution and that urea adsorption onto activated carbon followed a pseudo-second-order kinetic model. We classified the urea adsorption on activated carbon as physical adsorption and found that it was best described by the Halsey adsorption isotherm, suggesting that the multilayer adsorption of urea molecules on the adsorption sites of activated carbon best characterized the adsorption system. The mechanism of adsorption of urea by activated carbon involved two steps. First, an amino (–NH2 ) group of urea interacted with a carbonyl (–C˭O) group and a hydroxyl (−OH) group on the surface of activated carbon via dipole–dipole interactions. Next, the –C˭O group of the urea molecule adsorbed to the activated carbon interacted with another –NH2 group from a second urea molecule, leading to multilayer adsorption. GRAPHICAL ABSTRACT: Schematic representation of the adsorption of urea on activated carbon.